Pelatihan Berpikir Positif untuk Mencegah Stres Dikalangan Siswa SMA Kecamatan Manggis Kabupaten Karangasem - I Wayan Candra; I Nengah Sumirta; I Gusti Ayu Harini (Poltekkes Kemenkes Denpasar, 2019)
Student learning experiences stress. Hence the need for adaptation constructive efforts to overcome them, one of them with positive thinking. The general objective of the activities carried out by this dedication is to improve the knowledge and skills of students SMA Manggis about positive thinking. Community activity service performed using the method of training to the target audience of 40 persons are students SMA Manggis. The result shows the lowest score is 30 and the highest value is 70. After community services by providing training showed an increased ability of students to understand the material stress and the ability of visualization. A total of 40 persons 100% of students of the SMA Manggis show has been an increased understanding of stress and visualization. Obtained a minimum score is 70 and the maximum score is 100, it indicates that the mastery of students' understanding of visualization has reached at least 70%. The ability of students to do positive thinking techniques correctly reaches 70% (28 people). Paired Samples Test result -14.74, p=0.000. Keywords: Training positive thinking, stress.